TANTANGAN PENGKAJIAN ISLAM DALAM BIDANG TEOLOGI DI MALAYSIA - Mohd Fauzi Hamat (State Islamic University North Sumatra, 2009)
Abstract: The Challenges of Islamic Studies on Theology in Malaysia. Theology is a branch of Islamic Studies specifically designed to safeguard Islamic tenets and ideology from outsiders’ attact throughout history. In Malaysia, the study of theology has been carried out from the pesantren era of Islamic Kingdoms to the present day era of universities. Some of the universities that offer this course work include Academy of Islamic Studies, University of Malaya, Faculty of Islamic Studies, and National University of Malaysia. The author argues that nowadays, the study of theology in Malaysia is facing some predicaments from some schools of thought, such as Liberal Islam, Shi’ism, and Wahhabism. These schools of thought and new challenging trends have to be faced with certain steps by those in charge of designing curriculum of theology. This article attempts to suggest some steps and mechanism to ensure that the study of theology can keep up in pace with future developments.Kata Kunci: pengkajian Islam, teologi, manhaj